2012
DOI: 10.1371/journal.pone.0049532
|View full text |Cite
|
Sign up to set email alerts
|

Two Heterozygous Mutations in NFATC1 in a Patient with Tricuspid Atresia

Abstract: Tricuspid Atresia (TA) is a rare form of congenital heart disease (CHD) with usually poor prognosis in humans. It presents as a complete absence of the right atrio-ventricular connection secured normally by the tricuspid valve. Defects in the tricuspid valve are so far not associated with any genetic locus, although mutations in numerous genes were linked to multiple forms of congenital heart disease. In the last decade, Knock-out mice have offered models for cardiologists and geneticists to study the causes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 49 publications
1
15
0
1
Order By: Relevance
“…The identified missense changes result in a variably defective NFATC1 nuclear import and transcriptional function in vitro, and dramatically impact cardiac development in vivo, supporting their functional and clinical relevance. These results are in agreement with previous studies reporting the identification of NFATC1 variants and CNVs encompassing the gene in patients with various congenital heart defects, including ventricular septal defects and tricuspid atresia (Abdul‐Sater et al., ; Feng et al., ; Gu et al., ; Han et al., ; Khalil et al., ; Li et al., ; Shen et al., ; Wang et al., ; Yehya, Souki, Bitar, & Nemer, ; Zhao et al., ). These results are also in agreement with previous identification of AVSD‐related variants in CRELD1 , a gene acting as a regulator of calcineurin/NFATC1 signaling by promoting NFATC1 dephosphorylation and translocation to the nucleus.…”
Section: Discussionsupporting
confidence: 92%
“…The identified missense changes result in a variably defective NFATC1 nuclear import and transcriptional function in vitro, and dramatically impact cardiac development in vivo, supporting their functional and clinical relevance. These results are in agreement with previous studies reporting the identification of NFATC1 variants and CNVs encompassing the gene in patients with various congenital heart defects, including ventricular septal defects and tricuspid atresia (Abdul‐Sater et al., ; Feng et al., ; Gu et al., ; Han et al., ; Khalil et al., ; Li et al., ; Shen et al., ; Wang et al., ; Yehya, Souki, Bitar, & Nemer, ; Zhao et al., ). These results are also in agreement with previous identification of AVSD‐related variants in CRELD1 , a gene acting as a regulator of calcineurin/NFATC1 signaling by promoting NFATC1 dephosphorylation and translocation to the nucleus.…”
Section: Discussionsupporting
confidence: 92%
“…Genomic alterations in the NFATc1 locus have been identified in patients with CHD (Yehya et al, 2006) and recently, heterozygous mutations in NFATc1 have been identified in a patient with tricuspid atresia (Abdul-Sater et al, 2012). Further research is necessary to determine whether additional point mutations in NFATC1 and its regulatory genes in the NFATC1 signaling pathway (Crabtree and Olson, 2002; Rao, 2009) are associated with congenital heart valve malformations.…”
Section: Conclusion and The Direction Of Future Researchmentioning
confidence: 99%
“…The pathogenesis of TA remains unknown, though an underlying genetic cause is suspected in at least some cases, supported by evidence from mice studies (14-16) as well as familial cases (17). A recent clinical genetic study of a patient with tricuspid atresia revealed two heterozygous mutations in NFATC1 (12), a gene previously discovered to be essential in valvular formation in mice (15)(16). Exocrine function was thought to be maintained in our patient as she had no history of weight loss or steatorrhea.…”
Section: Discussionmentioning
confidence: 66%
“…Tricuspid atresia (TA) is a rare cardiac malformation, representing only 1% of all congenital heart disease (12)(13). TA is a cyanotic malformation that presents as an absence of the tricuspid valve, effectively removing the direct conduit between the right atrium and ventricle (12). The pathogenesis of TA remains unknown, though an underlying genetic cause is suspected in at least some cases, supported by evidence from mice studies (14-16) as well as familial cases (17).…”
Section: Discussionmentioning
confidence: 99%